Work overload of Nursing professionals: interface factors to Burnout Syndrome (Research, Society and Development, 2022)
Objective: to identify in the literature which factors influence the workload of nursing  professionals and its interface with the Burnout Syndrome. Methodology: this is na integrative review with a qualitative approach and descriptive character, with a time frame from 2012 to 2021, the electronic database selected for Search was BVS because it includes the bases SCIELO and LILACS. The articles weew selected first by Reading the title, later by the abstracts and finally, full reading. Results: there was a total of nine publications that designed the research criteria, as They include a theoretical constructo for this review. Final considerations: it enabled the identification of contributing factors for the burnout syndrome and the need to conduct research on reflections on possible strategies for coping with the syndrome. Greater investments are needed in studies on Burnout Syndrome, as intervention strategies must be elucidated to be applied in an urgency or emergency in Public Health, allowing prevention, adequate treatment and intervention when necessary, favoring the reduction of professionals affected by the syndrome.